Cropping systems modulate the rate and magnitude of soil microbial autotrophic CO2 fixation in soil - Wu, Xiaohong; Ge, Tida; Wang, Wei; Yuan, Hongzhao; Wegner, Carl-Eric; Zhu, Zhenke; Whiteley, Andrew S.; Wu, Jinshui (Frontiers in Microbiology, 2015)
The effect of different cropping systems on CO2 fixation by soil microorganisms was studied by comparing soils from three exemplary cropping systems: continuous cropping of paddy rice (rice-rice), rotation of paddy rice and rapeseed (rice-rapeseed), and rotated cropping of rapeseed and corn (rapeseed-corn). Soils from different cropping systems were continuously labeling with 14C-CO2 for 110 days. The CO2-fixing bacterial communities were investigated by analyzing the cbbL gene encoding ribulose-1,5-bisphosphate carboxylase oxygenase (RubisCO). Abundance, diversity and activity of cbbL-carrying bacteria were analyzed by quantitative PCR, cbbL clone libraries and enzyme assays. After 110 days incubation, substantial amounts of 14C-CO2 were incorporated into soil organic carbon (14C-SOC) and microbial organic carbon (14C-MBC). Rice-rice rotated soil showed stronger incorporation rates when looking at 14C-SOC and 14C-MBC contents. These differences in incorporation rates were also reflected by RubisCO activities. 14C-MBC, cbbL gene abundances and RubisCO activity were found to correlate significantly with 14C-SOC, indicating cbbL-carrying bacteria to be key players for CO2 fixation in these soils. The analysis of clone libraries revealed distinct cbbL-carrying bacterial communities for the individual soils analyzed. Most of the identified operational taxonomic units (OTU) were related to Nitrobacter hamburgensis, Methylibium petroleiphilum, Rhodoblastus acidophilus, Bradyrhizobium, Cupriavidus metallidurans, Rubrivivax, Burkholderia, stappia and Thiobacillus thiophilus. OTUs related to Rubrivivax gelatinosus were specific for rice-rice soil. OTUs linked to Methylibium petroleiphilum were exclusively found in rice-rapeseed soil. Observed differences could be linked to differences in soil parameters such as SOC. We conclude that the long-term application of cropping systems alters underlying soil parameters, which in turn selects for distinct autotrophic communities.